Efficacy of Naproxen/Fexofenadine (SJP-003) in the Prevention of Side Effects of Influenza Vaccination: Four Case Studies - Pantea Kiani; Thomas A. Dahl; Jacqueline M. Iversen; Andrew Scholey; Joris C. Verster (Clinics and Practice, 2022)
The influenza virus is associated with sickness, and in particular among vulnerable populations such as elderly and those with underlying disease with hospitalization and increased mortality rates. Vaccination is an effective way to prevent infection with influenza. However, undesirable side effects of the vaccination are commonly experienced, and comprise one of the primary reasons for a substantial group of individuals to refrain from vaccination. An effective treatment against vaccination side effects could increase the overall willingness to vaccinate against influenza. Here, four cases are presented that self-administered SJP-003 (a combination of 220 mg naproxen sodium, directly followed by a single oral dose of 60 mg fexofenadine HCL), 2 h before and 10 h after influenza vaccination. No flu-like symptoms and pain at the injection site were reported. These observations warrant further investigation of SJP-003 in double-blind, placebo-controlled clinical trials.